2008
DOI: 10.1016/j.molcel.2008.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Complete Integrin Ectodomain in a Physiologic Resting State and Activation and Deactivation by Applied Forces

Abstract: The complete ectodomain of integrin αIIbβ3 reveals a bent, closed, low-affinity conformation, the β-knee, and a mechanism for linking cytoskeleton attachment to high affinity for ligand. Ca and Mg ions in the recognition site, including the synergistic metal ion binding site (SyMBS), are loaded prior to ligand binding. Electrophilicity of the ligand-binding Mg ion is increased in the open conformation. The β3 knee passes between the β3-PSI and αIIb-knob to bury the lower β-leg in a cleft, from which it is rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
807
4
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 453 publications
(856 citation statements)
references
References 47 publications
(112 reference statements)
42
807
4
3
Order By: Relevance
“…Previous work showed that tetraspanins stabilize integrins in their active conformations [13] and that CD9 promotes β1 activation [14]. Activation of LFA-1 integrin is regulated by the actin linker protein talin [15], which has been implicated in integrin "inside-out" signaling [16]. However, talin relocalization to the IS in CD9-and CD151-silenced T cells remained similar to control cells (Supporting Information Fig.…”
mentioning
confidence: 86%
“…Previous work showed that tetraspanins stabilize integrins in their active conformations [13] and that CD9 promotes β1 activation [14]. Activation of LFA-1 integrin is regulated by the actin linker protein talin [15], which has been implicated in integrin "inside-out" signaling [16]. However, talin relocalization to the IS in CD9-and CD151-silenced T cells remained similar to control cells (Supporting Information Fig.…”
mentioning
confidence: 86%
“…This is followed by the β-subunit stalk/leg section that contains four cysteine-rich integrin epidermal growth factor-like (I-EGF) modules, before the β-ankle TM domain and a cytoplasmic tail (Shi et al 2005;Zhu et al 2008). Both the α-and β-cytoplasmic tails have no actin-binding or enzymatic activity and instead act as a hub for adaptor protein complex assembly (Zhu et al 2008). Interestingly, the β-tails are more highly conserved that the α-tails and are the primary moderator of intracellular ligand interactions.…”
Section: β-Subunitmentioning
confidence: 99%
“…Investigations into the type of integrins found within lamellipodia and filopodia have revealed that β1 integrins are preferentially concentrated in clusters at the ends of both (Galbraith et al 2007), whereas β3 integrins require activation before they can be assembled in filopodia or lamellipodia. This assembly can occur through either the binding of intracellular adaptor proteins to initiate inside-out activation or by binding of the extracellular ligand to initiate outside-in activation (Zhu et al 2008). In contrast, podosomes and Fig.…”
Section: Cellular Protrusions During Migrationmentioning
confidence: 99%
“…This bidirectional force transmission is a crucial aspect of integrin function. Structural studies provide evidence that integrins react to application of force by altering their conformational state from inactive to active (Jin et al, 2004;Katsumi et al, 2005;Alon and Dustin, 2007;Zhu et al, 2008). In their resting state prior to contact with the extracellular matrix, integrin heterodimers are mostly in an inactive conformation, with their extracellular regions bent and their very short cytoplasmic domains held together by a non-covalent salt bridge.…”
Section: Force and Sarcolemmal Adhesion Site Assemblymentioning
confidence: 99%
“…In their resting state prior to contact with the extracellular matrix, integrin heterodimers are mostly in an inactive conformation, with their extracellular regions bent and their very short cytoplasmic domains held together by a non-covalent salt bridge. The association of the actin-binding protein talin with the ␤ tail of integrin, which permits cell-generated lateral pulling forces to be applied to the ␤ tail, results in disruption of the clasp and subsequent separation of the transmembrane segments (Burridge et al, 1997;Zhu et al, 2008) (Fig. 2).…”
Section: Force and Sarcolemmal Adhesion Site Assemblymentioning
confidence: 99%